2021
DOI: 10.21203/rs.3.rs-370652/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mortality Rate and Years of Life Lost Due to COVID-19 in Iran, Fars Province.

Abstract: Introduction: Corona became a public health threat worldwide in late 2019, in which its main target is lower airway. The aim of this study was to calculate the mortality rate and years of life lost due to COVID-19 in Iran.Method: All definite deaths due to COVID-19 from February 20, 2020 to the February 12, 2021 have been used. Descriptive analyzes included mean and standard deviation of age at death, the number and sex ratio of deaths. Then the age and sex-specific mortality rate were calculated. YLL were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…In terms of age distribution of disease burden, the findings of this study showed that age groups 60 years and older in both sexes have imposed more burden on society. This finding is also consistent with the findings of studies conducted in Iran (21), South Korea (19) and Italy (20). The higher incidence of the disease in the age group over 60 years can be considered a higher risk of disease and a higher risk of death in this age group (23,24).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of age distribution of disease burden, the findings of this study showed that age groups 60 years and older in both sexes have imposed more burden on society. This finding is also consistent with the findings of studies conducted in Iran (21), South Korea (19) and Italy (20). The higher incidence of the disease in the age group over 60 years can be considered a higher risk of disease and a higher risk of death in this age group (23,24).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the total disease burden for men and women per 1000 people was estimated to be 30.8 and 26.6 years, respectively. The sex difference observed in the burden of COVID-19 disease is consistent with the findings of studies conducted throughout Iran (17) and Fars Province (21) as well as studies conducted in South Korea (19) and Italy (20). The higher incidence observed in men than women can be due to gender differences in disease and death.…”
Section: Discussionsupporting
confidence: 87%